GORE® Cardioform ASD Occluder experience in transcatheter closure of "complex" atrial septal defects. Issue 1 (15th October 2021) - Santoro, Giuseppe; Cuman, Magdalena; Pizzuto, Alessandra; Haxhiademi, Dorela; Lunardini, Alessia; Franchi, Eliana; Marrone, Chiara; Pak, Vitali; Assanta, Nadia; Cantinotti, Massimiliano
Abstract: Objective: To evaluate the GORE® Cardioform ASD Occluder (GCO) (WL Gore & Associates, Flagstaff, AZ) device for "complex" atrial septal defects (ASD) closure. Background: Transcatheter ASD closure is still challenging in "complex" clinical/anatomic settings. This study evaluated the results of GCO in closure of "complex" ASD in a tertiary referral center. Methods: Between January 2020 and March 2021, 72 patients with significant ASD were submitted to transcatheter closure with GCO at our Institution. Based on clinical/anatomic characteristics, they were classified as "complex" ( n  = 36, Group I) or "simple" ( n  = 36, Group II). We considered as "complex", defects with rim deficiency (< 5 mm) other than antero‐superior, relatively large (diameter/patient weight > 1.2 or diameter/patient BSA > 20 mm/m 2 ) or within a multifenestrated septum. Procedure results and early outcome were compared between the groups. Results: Absolute and relative ASD size (20 ± 4 vs. 15 ± 3 mm, p  < 0.0001; 0.9 ± 0.3 vs. 0.4 ± 0.2 mm/kg, p  < 0.0001; 23 ± 7 vs. 12 ± 5 mm/m 2, p  < 0.0001), QP/QS (2.0 ± 0.8 vs. 1.4 ± 0.3, p  < 0.001), procedure and fluoroscopy times (73 ± 36 vs. 43 ± 21 min, p  < 0.0001; 16 ± 9 vs. 9 ± 4 min, p  < 0.0001, procedure feasibility (94.4 vs. 100%, p  < 0.0001) and overall complication rate (13.9 vs. 0%, p  < 0.0001) were significantly different between the groups. Successful closure of "surgical" ASDs was achieved in 92% of cases. Complete closure at last follow‐up evaluation did not significantly differ between the groups (97.1 vs. 100%, p  = NS), as was wireframe fractures rate (49.1% in the overall population), without clinical, EKG and echocardiographic consequences. Conclusions: Percutaneous treatment with GCO device is effective and safe in high percentage of "complex" ASDs.